(3eNJUQ aj GdSjQI GdfHhjIs - (3YR GdOjf YHO GdYRjR Hf eMeO Hf GHQgje Hf LeGYI GdcfGfjs ((3JLGg GdcYHI GdeYXeI s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai LRjd fYeGFg CeG HYO agPG eNJUQ ai SjQI SjOfG QShd Gddg Udi Gddg Ydjg hSde LeYJg ef cJH ai GdeZGRi hGdSQ s
(3BNQgG (B:s
(3ai PcQ Oafg Udi Gddg Ydjg hSde (B: ( (3hbHd jhe GdCQHYGA Udi Gddg Ydjg hSde hYdi Bdg hUMHg hSde JSdekG cKjQkG OGFekG Edi jhe GdOjf Je GdeNJUQ GdcHjQ (B) s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bhHdJ Ydi GdfSNI GdJi HNW GdeUfa hgj HjOgs
(3hGdChQGb GdChdi efgG HNW CMOK Yf SGFQgG s
(3hai UOQgG Jedc YHO Gddg GdOfhTQi GdCRgQi dgG SfI (B994(3g` s
(3hai BNQ GdfSNI SeGYGJ Ydi GdeDda SfJi (B736(3, (B754 s
Keywords: (3GdJGQjNs